PRACTICE TEACHING IN CANADA’S INDEPENDENT SCHOOLS - Bérard, Robert Nicholas; Murphy, H. Joseph (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1993)
Recognizing the need to broaden our understandings of the nature of the process by which student teachers are inducted into the profession, several teacher educators have called upon researchers to give special attention to the varying contexts of student teaching. This study reports the experiences as supervisors of practice teaching of a unique group of educators, the headmasters and headmistresses of over 50 of Canada’s private or independent schools. We analyze their responses and compare them with the experiences of the authors as teacher educators in Nova Scotia. We discuss the advantages and disadvantages associated with practice teaching in the traditional private school. RÉSUMÉ Reconnaissant la nécessité d’approfondir notre compréhension du processus selon lequel nous initions les stagiaires à la profession, plusieurs formateurs de maîtres ont invité les chercheurs en éducation de porter une attention toute particulière aux divers contextes de la formation pratique. Nous rapportons dans cette étude les expériences-dans leur rôle de surveillants de formation pratique d’un groupe spécial d’éducateurs-des directeurs et directrices de plus de 50 écoles privées ou indépendantes du Canada. Nous analysons leurs réponses et les comparons aux expériences des chercheurs conune formateurs de maîtres en Nouvelle-Écosse. Nous discutons des avantages et des désavantages associés à laformation pratique dans l’école privée traditionnelle.